Regional Dichotomy in Enteric Mucosal Immune Responses to a Persistent Mycobacterium avium ssp. paratuberculosis Infection - Facciuolo, Antonio; Lee, Amy H.; Gonzalez Cano, Patricia; Townsend, Hugh G. G.; Falsafi, Reza; Gerdts, Volker; Potter, Andrew; Napper, Scott; Hancock, R. E. W.; Mutharia, Lucy M.; Griebel, Philip J. (Frontiers in Immunology, 2020)
Chronic enteric Mycobacterium avium ssp. paratuberculosis (MAP) infections are endemic in ruminants globally resulting in significant production losses. The mucosal immune responses occurring at the site of infection, specifically in Peyer’s patches (PP), are not well understood. The ruminant small intestine possesses two functionally distinct PPs. Discrete PPs function as mucosal immune induction sites and a single continuous PP, in the terminal small intestine, functions as a primary lymphoid tissue for B cell repertoire diversification. We investigated whether MAP infection of discrete versus continuous PPs resulted in the induction of significantly different pathogen-specific immune responses and persistence of MAP infection. Surgically isolated intestinal segments in neonatal calves were used to target MAP infection to individual PPs. At 12 months post-infection, MAP persisted in continuous PP (n=4), but was significantly reduced (p=0.046) in discrete PP. RNA-seq analysis revealed control of MAP infection in discrete PP was associated with extensive transcriptomic changes (1,707 differentially expressed genes) but MAP persistent in continuous PP elicited few host responses (4 differentially expressed genes). Cytokine gene expression in tissue and MAP-specific recall responses by mucosal immune cells isolated from PP, lamina propria and mesenteric lymph node revealed interleukin (IL)22 and IL27 as unique correlates of protection associated with decreased MAP infection in discrete PP. This study provides the first description of mucosal immune responses occurring in bovine discrete jejunal PPs and reveals that a significant reduction in MAP infection is associated with specific cytokine responses. Conversely, MAP infection persists in the continuous ileal PP with minimal perturbation of host immune responses. These data reveal a marked dichotomy in host-MAP interactions within the two functionally distinct PPs of the small intestine and identifies mucosal immune responses associated with the control of a mycobacterial infection in the natural host.